Polymerization‐Induced Thermal Self‐Assembly of Functional and Thermo‐Responsive Diblock Copolymer Nano‐Objects via RAFT Aqueous Polymerization. Issue 2 (20th November 2018) - Vakili, Mohammad; Cunningham, Victoria J.; Trebbin, Martin; Theato, Patrick
Abstract: The polymerization‐induced self‐assembly (PISA) of amphiphilic diblock copolymer nano‐objects, which are synthesized via reversible addition‐fragmentation chain‐transfer (RAFT) aqueous polymerization, is discussed. First, the effectiveness of the ( S )‐2‐(ethyl propionate)‐( O ‐ethyl xanthate) as a RAFT chain transfer agent for the polymerization of N, N ‐dimethylacrylamide (DMAm) yielding a water‐soluble macro RAFT agent is investigated. In a second step, poly(DMAm) macro‐CTA is chain‐extended with acrylate monomers in water inducing a PISA process. Besides the use of pentafluorophenyl acrylate (PFPA) as core‐forming block, the thermo‐responsive nature of N ‐isopropylacrylamide (NIPAm) and the reactive character of pentafluorophenyl acrylate (PFPA) for a subsequent post‐modification is exploited. Monomer conversion and reaction kinetics are determined via nuclear magnetic resonance spectroscopy, while gel permeation chromatography is used to evaluate the molecular weight distribution of the polymers. The obtained spherical nanostructures are analyzed via dynamic light scattering, scanning electron microscopy, transmission electron microscopy and atomic force microscopy. Abstract : Diblock copolymer micelles with poly(NIPAm) and poly(PFPA) as core‐forming block are synthesized at room temperature via RAFT upon UV‐initiation and use of redox initiator couples, respectively. Cross‐linking of reactive poly(PFPA) cores and coronas enables imaging via AFM and electron microscopy. Polymerization‐induced thermal self‐assembly of poly(NIPAm)‐ block ‐poly(PFPA) nanoparticles shows linear relationship between particle size and degree of polymerization.